Penatalaksanaan Fisioterapi dengan Metode Core Stability dan Tandem Walking Exercise untuk Meningkatkan Keseimbangan pada Lansia - Anggun Dwigahayu; Wanti Hasmar; Adi Saputra Junaidi (Prosiding Seminar Kesehatan Nasional, 2022)
Â Elderly is someone who has entered the age of 60 years, the elderly experience various changes both physically, mentally, and socially. Changes that are physical, stamina, and appearance. One of the physical changes experienced by the elderly is balance disorders. Balance disorders that occur in the elderly are caused by changes in the neurological or central nervous system, the sensory system, especially the visual system, proprioception, and changes in the vestibular and musculoskeletal systems. To find out the management of physiotherapy in conditions of balance disorders with the core stability and tandem walkingÂ  exercise can improve balance and in the elderly. After six therapeutic actions with core stability exercise using bridging exercise techniques for four times a week with six repetitions and tandem exercise walking three times a week with 3-6 meters, the results showed an increase in balance and an increase in the ability of functional activities. Core stability and walking tandem exercise can improve balance and improve the ability of functional activities in the elderly.Â